THE DESCRIPTION OF 6TH GRADE ELEMENTARY STUDENTS’ KNOWLEDGE ABOUT DENGUE HEMORAGIC FEVER (DHF) - Siti Anisatur Rokhmah (Indonesian Journal of Health Development, 2021)
Dengue Hemoragic Fever (DHF) is an infectious disease that is a problem of the health of the Indonesian people. West Java is the province with the most cases occurred, and that is 10.016 cases. DHF could be lethal and it happens to grade-schooler especially the elementary students according to the health ministry in the year 2018. This research aims to measures students' knowledge. This research used descriptive type of research, with the population of the research is the whole 6th-grade elementary students at SD Negeri Babelan Kota 07. Sample taking of this research uses the purposive sampling method. The result of the analysis from 73 respondents found that 39 respondents (53,4%) are in the good level of knowledge category, 26 respondents (35,6%) are at an adequate level, and 8 respondents are at an inadequate level of knowledge category. The level of knowledge about DHF in research respondents is in the good category. Suggestion for further research to plan the implementation of health promotion because there are still students who have only sufficient knowledge and lack knowledge of transmission, prevention, and the 3M Plus program for dengue fever.